Rapid evidence profile #89: Self-testing for gynecological and urological conditions - Waddell, K; Dass, R; Whitelaw, H; Sivanesanathan, T; Grewal, E; Ali, A; Phelps, A; Wilson, MG (My University, 2025)
An overview of the best available research evidence from around the world (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about self-testing for gynecological and urological conditions in response to a decision-maker’s request.
Keywords: self-testing; gynecological; urological; conditions